Pengaruh Signifikan Kehadiran Pasar Modern (Indomaret Dan Alfamart) Terhadap Keberlangsungan UMKM Di Kelurahan Malawili, Kabupaten Sorong - Nurhayati Suhajatno; Fanny Jitmau (Prodi Ekonomi Syariah IAIN Sorong, 2025)
The study used quantitative methods and regression analysis techniques to determine the partial effect. The results indicate that the presence of modern markets has a significant partial effect on the sustainability of MSMEs. The presence of modern markets creates a fairly strong competitive impact, requiring MSMEs to adapt to changing consumer preferences. Consumers tend to choose modern markets because of their convenience and more competitive prices.The implications of these findings suggest that MSMEs improve product quality, service innovation, and marketing strategies. Local governments are advised to formulate modern market zoning policies that favor MSMEs and provide relevant mentoring and training programs. These findings provide an important contribution to efforts to maintain a balance between economic modernization and MSME sustainability.